Digital play in early childhood - Sakr, Mona (SAGE, 2020)
"Critically examining the fears that commonly surround young children's play involving digital technologies, this book seeks to address each of the negatives and present the positive possibilities of technology when it comes to early childhood. Using observations of children in play and cutting-edge research, this book will empower students and build their confidence so that they are able to challenge perceptions and think creatively about how they can use technology. Each chapter includes case studies, research spotlights, activities and annotated further reading to help students develop their critical thinking, deepen their research and connect theory with practice."- Resumé vydavatel
Keywords: didaktická technika -- sociální aspekty; hra; inovace; základní vzdělávání; digitální technologie; educational technology -- social aspects; play; innovations; elementary school education; digital technologies; elektronické knihy; monografie; electronic books; monographs